Influence of suit size and air permeability on performance in ski jumping. Part I: wind tunnel measurements - Virmavirta, Mikko; Müller, Sören; Kürschner, Mario; Bessone, Veronica; Krężałek, Piotr; Elfmark, Ola (Frontiers in Sports and Active Living, 2025)
In the first of a two-part study, the purpose was to investigate the influence of suit size and air permeability on ski jumping performance using wind tunnel measurements and numerical simulations. Results demonstrated that suit size greatly influenced aerodynamic performance, with drag increasing by ∼4% and lift by ∼5% for every 2 cm increase in tolerance. Changes in air permeability remained within the limits of measurement accuracy. Numerical simulations revealed an average difference of 5.8 m between suits of different sizes, corresponding to an increase of 2.8 m per cm of tolerance, based on a simulated reference jump of 130 m at Granaasen HS-138 m. The numerical simulations also highlighted that factors such as length of the reference jump, wind conditions, and altitude influenced performance difference. In summary, this investigation underscores the importance of suit size, as well as restricted importance of air permeability, on ski jumping performance, thereby enhancing the understanding of the role of equipment in the sport.